Functional quadriceps reconstruction: 3D gait analysis, EMG and environmental simulator outcomes. Issue 11 (November 2022) - Lo, Steven; Childs, Craig; Mahendra, Ashish; Young, Peter; Carse, Bruce
Abstract: Object: Limited objective evidence exists on the benefits of functional muscle transfers following quadriceps resection in sarcoma. In particular, no studies have compared patients with functional transfers to those without. In this study, objective and subjective assessments were performed with 3D Gait Analysis, Environmental Simulator, Electromyography (EMG) and Patient-Reported Outcomes. Methods: Thirty-four patients at the Scottish Sarcoma Network Glasgow Centre/ Canniesburn Plastic Surgery Unit underwent quadriceps resection for sarcoma between 2009 – 2019, including 24 patients with functional reconstruction and 10 without. Both groups were equivalent for the extent of quadriceps resection (2.58 versus 2.85 components, p=0.47). Primary outcome measure was 3D Gait Analysis and Gait Profile Score (GPS), and secondary outcome was the Toronto Extremity Salvage Score (TESS) score. Ancillary analyses included environmental simulation with the Motek CAREN system and EMG of transferred muscles. Results: Outcomes measures were better in functional reconstruction patients when compared to those without – the GPS score was 8.04 versus 10.2 (p=0.0019), and the TESS score was 81.85 versus 71.17 (p=0.028). Environmental simulator tasks found that functional reconstruction patients could complete activities of daily living including shopping and collision avoidance tasks, without significantly slowing their walking speed. Patients without a functional reconstruction could not complete weighted shopping tasks. EMG showed that transferred hamstrings co-activated with the ipsilateral rectus femoris during the gait cycle. Conclusions: These are the first objective data demonstrating the superiority of muscle transfers for functional restoration in quadriceps resection versus patients without functional transfers. Critically, these also provide answers to patient-oriented questions relating to the recovery of function and activities of daily living.